The Comfort Ability Pain Management Workshop: A Preliminary, Nonrandomized Investigation of a Brief, Cognitive, Biobehavioral, and Parent Training Intervention for Pediatric Chronic Pain. (18th September 2017) - Coakley, Rachael; Wihak, Tessa; Kossowsky, Joe; Iversen, Christina; Donado, Carolina
Abstract: Objective: Psychological intervention is widely recognized as an integral part of the recovery process from pediatric chronic pain, but service acquisition is often limited by resource barriers. The aim of this study was to assess the feasibility, acceptability, and satisfaction of a brief, structured, skills-based, group intervention designed expressly to address gaps in service delivery. Exploratory outcomes were also assessed. Method: Adolescents with chronic pain ( n  = 102; ages 10–17 years) and their mothers ( n  = 105) completed self-report questionnaires at baseline, 1-week, 1-month, and 3-month posttreatment. Results: This study demonstrated feasibility, and overall high acceptability and satisfaction among adolescents and parents. Exploratory analyses within this nonrandomized design suggest that adolescents demonstrate improvement in functionality ( p = .0012), depression symptoms ( p < .0001), and pain catastrophizing ( p < .0001) by 1-month posttreatment and continued making gains over time. Parents made significant changes in parenting practices ( p- values < .01) and in their beliefs about their adolescent's ability to manage pain ( p < .001) by 1-week posttreatment and continued making gains over time. Conclusions: This brief intervention is both feasible and acceptable. Although small effect sizes were found for all outcome measures, parents and adolescents made significant gains postintervention. In the absence of a direct comparison group, we cannot determine if these improvements are exclusively attributable to the intervention. Future research will be needed to understand the degree to which this brief intervention may effectively enhance the attainment of evidence-based psychoeducation and cognitive behavioral skills that are known to foster adaptive parent and adolescent responses to chronic pain.